Analysis Of Elderly Anxiety On The Level Of Independence At The Tresna Werdha Blitar Social Service Unit In Tulungagung - Naya Adhisa Paramitha; Dedi Saifulah (Universitas STRADA Indonesia, 2026)
The elderly are prone to experiencing anxiety due to physical, psychological, social, and economic changes that can affect the level of independence in daily activities. This research is important to understand the relationship between anxiety and independence of the elderly in the social care environment. This study uses a quantitative design with a cross sectional approach. The research population was all elderly at the Tresna Werdha Blitar Social Service Unit in Tulungagung, with a sample of 36 respondents using the total sampling technique. The research instruments included the GAD-7 questionnaire to measure anxiety and the Barthel ADL Index to assess the level of independence. Data analysis was carried out using the Spearman's rho test.The results showed that the majority of the elderly had a minimum level of anxiety as many as 17 respondents (47%), mild anxiety 14 respondents (39%), and moderate anxiety 5 respondents (14%). The level of independence of the elderly is mostly in the category of mild dependency as many as 22 respondents (61%). The Spearman's rho test showed a significant relationship between anxiety levels and independence levels with a value of p = 0.032 (p < 0.05).These findings indicate that the lower the level of anxiety, the higher the independence of the elderly. Psychological, physical, and social anxiety management interventions need to be optimized to increase the independence of the elderly in social institutions.